The outcome of the surgical treatment of pelvic chondrosarcomas: a competing risk analysis of 58 tumours from a single centre. (May 2017) - Stihsen, C.; Panotopoulos, J.; Puchner, S. E.; Sevelda, F.; Kaider, A.; Windhager, R.; Funovics, P. T.
Abstract : Aims: Few studies dealing with chondrosarcoma of the pelvis are currently available. Different data about the overall survival and prognostic factors have been published but without a detailed analysis of surgery-related complications. We aimed to analyse the outcome of a series of pelvic chondrosarcomas treated at a single institution, with particular attention to the prognostic factors. Based on a competing risk model, our objective was to identify risk factors for the development of complications. Patients and Methods: In a retrospective single-centre study, 58 chondrosarcomas (26 patients alive, 32 patients dead) of the pelvis were reviewed. The mean follow-up was 13 years (one week to 23.1 years). Results: A total of 26 patients (45%) were alive and 32 patients (55%) had died. Overall survival was 76%, 55% and 45% at one, five and ten years post-operatively, respectively. In a competing risk model the cumulative risk of the development of a surgery-related complication was 64% at six months and 69% at one year, post-operatively, respectively. Endoprosthetic reconstruction was a significant risk factor for the development of complications (p = 0.006). Complications were not significantly related to age or the location or grade of the tumour (p = 0.823, p = 0.976, p = 0.858). The development of complications did not have a negative effect on survival (p = 0.147). Conclusion: This is the first study with competing risk analysis of surgery-related complications in patients with a pelvic chondrosarcoma. The surgery in these patients remains prone to complications. Endoprosthetic reconstruction significantly increases the risk of the development of complications (p = 0.006). A competing risk model showed that the development of complications does not have a negative influence on overall survival (p = 0.147). An aggressive, surgical resection with the goal of achieving wide margins whenever possible remains the mainstay of treatment. Cite this article: Bone Joint J 2017;99-B:686–96.